2014
DOI: 10.1016/j.jcp.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Fluid preconditioning for Newton–Krylov-based, fully implicit, electrostatic particle-in-cell simulations

Abstract: A recent proof-of-principle study proposes an energy-and charge-conserving, nonlinearly implicit electrostatic particle-in-cell (PIC) algorithm in one dimension [Chen et al, J. Comput. Phys., 230 (2011) 7018].The algorithm in the reference employs an unpreconditioned Jacobian-free Newton-Krylov method, which ensures nonlinear convergence at every timestep (resolving the dynamical timescale of interest). Kinetic enslavement, which is one key component of the algorithm, not only enables fully implicit PIC a prac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
(54 reference statements)
1
41
0
Order By: Relevance
“…Of course, the grid spacing introduces a numerical error in the current accumulation and interpolation routines. Finally, although a preconditioned version of the fully-implicit PIC has been presented in [60], we use the unpreconditioned version here, so that both method are unpreconditioned. Since the focus of this work is on the discretization in velocity space, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the grid spacing introduces a numerical error in the current accumulation and interpolation routines. Finally, although a preconditioned version of the fully-implicit PIC has been presented in [60], we use the unpreconditioned version here, so that both method are unpreconditioned. Since the focus of this work is on the discretization in velocity space, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Using these techniques, the numerical stability is greatly improved (with respect to explicit PIC), but energy is still not conserved exactly and, at each time step, there is a small inconsistency between the charge and current densities calculated from the particles and the one that is used for advancing the fields. Some authors have suggested that such limitations are responsible for the accumulation of numerical errors that preclude semi-implicit PIC simulations to run for long time intervals [54,60]. Recently, however, [61] and [54] have formulated and successfully implemented a fully-implicit, one-dimensional PIC code (see also [62] for an electromagnetic extension).…”
Section: Introductionmentioning
confidence: 99%
“…The first one is a piston-driven 1D slow magnetosonic wave shock problem, with a grid packed near the piston. Unlike earlier studies in implicit PIC algorithms [41,43,32,1], this example features an open system with non-periodic boundary conditions (inflow and perfect conductor). The second one is a 2D Weibel instability on a fully curvilinear grid based on a sinusoidal map deformation.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The main advantage of this method is the reduction of the memory requirements of the Krylov method because the particles have been brought out of the Krylov loop and only the filed quantities matter when computing the memory requirement. This approach is especially suitable to hybrid architectures (Chen et al, 2012) and can be made most competitive when fluid-based preconditioning is used Chen et al (2014). However, in the present case of a low dimensionality problem run on standard CPU computers, particle hiding is neither needed nor competitive.…”
Section: Newton-krylov Solversmentioning
confidence: 99%